2017
DOI: 10.1007/s00213-017-4732-4
|View full text |Cite
|
Sign up to set email alerts
|

Opiate dependence induces cell type-specific plasticity of intrinsic membrane properties in the rat juxtacapsular bed nucleus of stria terminalis (jcBNST)

Abstract: RATIONALE Drugs of abuse can alter circuit dynamics by modifying synaptic efficacy and/or the intrinsic membrane properties of neurons. The juxtacapsular subdivision of the bed nucleus of stria terminalis (jcBNST) has unique connectivity that positions it to integrate cortical and amygdala inputs and provide feed-forward inhibition to the central nucleus of the amygdala (CeA), among other regions. In this study, we investigated changes in the synaptic and intrinsic properties of neurons in the rat jcBNST durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…These are consistent with our results showing an elevated activity of BNST neuron activity. Opioid dependence, as elicited through chronic implant of a morphine pellet, also induces long-term potentiation (LTP) onto different populations of BNST cells ( Dumont et al, 2008 ; Francesconi et al, 2017 ), suggesting that plasticity onto BNST cell synapses may be a common feature of drugs of abuse, also consistent with our results. CRF may play a key role in this process because it increases the frequency of excitatory glutamatergic post-synaptic currents onto BNST cells that project to the VTA, a process occluded by ethanol withdrawal ( Silberman et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…These are consistent with our results showing an elevated activity of BNST neuron activity. Opioid dependence, as elicited through chronic implant of a morphine pellet, also induces long-term potentiation (LTP) onto different populations of BNST cells ( Dumont et al, 2008 ; Francesconi et al, 2017 ), suggesting that plasticity onto BNST cell synapses may be a common feature of drugs of abuse, also consistent with our results. CRF may play a key role in this process because it increases the frequency of excitatory glutamatergic post-synaptic currents onto BNST cells that project to the VTA, a process occluded by ethanol withdrawal ( Silberman et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…Pathway analysis revealed that genes implicated in synaptic long-term potentiation, synaptogenesis, and reelin signaling were among the most significantly associated with increased FOS correlation networks following chronic opiate exposure ( Table 1 ). Many drugs of abuse, including opioids, induce synaptic plasticity, suggesting that this type of neuroadaptation may be a common mechanism underlying the development of substance use disorders ( 29 31 ). Moreover, polymorphisms in genes associated with synaptic plasticity have been associated with vulnerability to drug addiction ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The BNST has been implicated in opioid withdrawal, drug-induced negative affect (114)(115)(116)(117), and the stress-induced reinstatement of drug seeking (118). BNST neurons are recruited during withdrawal to signal stress/aversion (119), measured by heightened Fos expression (120)(121)(122) and alterations of neuronal excitability during chronic exposure to and withdrawal from opioids (123)(124)(125). Opioid withdrawal-induced Fos immunoreactivity in the extended amygdala parallels the development of opioid-induced place aversion (122).…”
Section: Bed Nucleus Of the Stria Terminalismentioning
confidence: 99%